Motivational Factors for Substance Abuse Among Secondary School and University Students in Kenya: The Way Forward - Maithya, Redempta; M Muola, James; Mwinzi, Dinah (International Journal of Asian Social Science, 2012)
Substance abuse is becoming an increasing problem in Kenya. A number of studies carried out in the country show that almost every Kenyan youngster at one time or another experiments with substances, especially beer and cigarettes. A significant proportion of these young people eventually get addicted, posing a threat to their own health and safety while creating difficulties to their families and the public at large. This article reports on a quantitative and qualitative study which focused on motivational factors for substance abuse among secondary schools and university students in Kenya. The main objectives of the study were to: identify motivating reasons for substance use and effect of substance abuse on participation in academic activities. The views of students were investigated regarding their experiences with substance abuse. Both qualitative and quantitative approaches were used to gather and analyze data. The sample size was 360 secondary school students from 9 secondary schools; and 342 students from 3 Kenyan state universities. Among the major findings, the study revealed that students abused substances for various reasons including curiosity, acceptance by peers, ignorance mostly at the secondary school level; while at the university level they cited ability to forget individual problems besides enabling them to get euphoric in public gatherings. The salient findings of the study are that the transition of students from secondary school to university is sudden and dramatic, from an environment of complete control in the former to excess freedom in the latter. The study also noted that both males and females engage in substance abuse; there is a significant relationship between substance abuse and age, substance use by other family members and easy access to substances. Substance prevention education in both secondary and university levels were found to be inadequate in relation to instructional approaches, content and personnel skills. Lack of clear policies on prevention education and how to deal with substance abusers in educational institutions was cited to be a major barrier in attempts to address the vice in the institutions. The study makes a number of conclusions and recommendations in line with a comprehensive programme for prevention and intervention.